Application of miniprobe endoscopic ultrasonography in endoscopic submucosal dissection surgery for laterally spreading tumor of the rectum: a case report - Li, Lihong; Lv, Qianbao; Zhang, Tianpeng; Lai, Jinsong; Zhu, Dajian (Frontiers in Oncology, 2025)
BackgroundLaterally spreading tumor (LST) is a special clinical lesion occurring in the colorectum. Generally before surgery, it is necessary to identify whether the rectal submucosa and the muscularis propria are invaded or not. Miniprobe endoscopic ultrasonography (MEUS) is a convenient and advanced method for diagnosis of LST invasion of the wall of the rectum. Herein, we present a case of LST in the rectum to demonstrate the application of MEUS.Case descriptionA 49-year-old male patient who was found to have a flat mass in the rectum during an enteroscopy for physical examination, the pathological report of the biopsy of the LST revealed high-grade intraepithelial neoplasia, so the patient was admitted to our hospital. A systematic computed tomography(CT) scan showed slight thickening of the local rectal wall, with no evidence of regional lymph node metastasis or distant metastasis. To determine the depth of tumor invasion, MEUS was performed first, the result showed that the tumor, approximately 4 cm in diameter, was confined to the mucosal layer of the rectum, with intact submucosa and intrinsic muscular layer from the MEUS. Based on these findings, endoscopic submucosal dissection (ESD) was successfully performed. Final pathological diagnosis confirmed high-grade intraepithelial neoplasia with focal carcinomatosis, but the focal carcinoma did not invade the muscular layer of the rectal mucosa, both the horizontal and basal margins of the LST were negative for malignancy.ConclusionMEUS is an important and useful diagnostic method for identifying the depth of the invasion of LST in the rectum before ESD surgery, and ESD is an effective and safe procedure in the treatment of colorectal LSTs.